Effectiveness of Intensive Short-term Dynamic Psychotherapy on Rumination and Self-doubt Depressed Women Victims of Partner’s Infidelity - Jafari Dehnayebi, Maedeh; Kamalian, Maryam; Almasi, Reza; Rafiei, Zahra (Psychology of Woman Journal, 2025)
Objective: This study aimed to evaluate the effectiveness of Intensive Short-Term Dynamic Psychotherapy (ISTDP) in reducing rumination and self-doubt among depressed women who have experienced partner infidelity.Methods and Materials: A randomized controlled trial was conducted with 30 women aged 25 to 45 who reported betrayal by a male partner within the past year and met DSM-5 criteria for mild to moderate depression. Participants were recruited from mental health centers across Tehran and randomly assigned to an intervention group (ISTDP) or a waitlist control group. All participants completed the Ruminative Responses Scale (RRS) and Subjective Overachievement Scale (SOS) at baseline and post-intervention. The intervention group received ten weekly 60-minute ISTDP sessions based on Frederickson’s protocol, culturally adapted to the Iranian context. Mixed-design ANOVA was used to analyze pre- and post-test scores.Findings: Statistical analyses revealed significant time × group interaction effects for both rumination and self-doubt. Rumination scores in the ISTDP group decreased from M = 62.40 (SD = 8.21) at pretest to M = 48.20 (SD = 7.50) at posttest, while the control group showed minimal change. For rumination, F(1, 28) = 31.94, p < .001, partial η² = .53. Self-doubt scores dropped from M = 43.60 (SD = 6.95) to M = 32.67 (SD = 6.08) in the intervention group, with F(1, 28) = 27.13, p < .001, partial η² = .49. No significant main effects of group were found. All assumptions of ANOVA were met.Conclusion: ISTDP proved effective in significantly reducing rumination and self-doubt in depressed women who experienced partner infidelity. The findings support the utility of ISTDP as a culturally adaptable and emotionally focused intervention for cognitive-affective symptoms associated with relational trauma.